Study of Aluminum using Coating Powder and Without Coating Powder on the Rate of Corrosion in HCL Solution on Aluminum Alloy 7075 - Ananda, Andi Dwi; Latif2, Hendri Louis; Wahyu, Agnes Erna; Prayitno, Hadi (Formosa Journal of Applied Sciences, 2025)
Study This aims : 1) to find out results comparison rate corrosion between aluminum with powder coating and aluminum without powder coating to solution Sour Chloride , 2) knowing form Aluminum Alloy 7075 surface with powder coating and aluminum without powder coating to solution Sour Chloride , 3) produces impact test results to Aluminum Alloy 7075 with powder coating and aluminum without powder coating . Method research used is method type study descriptive quantitative . The data sources used is secondary data obtained direct from results study rate corrosion SEM testing and testing impact . Results from study This state that Aluminum Alloy 7075 with powder coating has rate more corrosion slow compared to without powder coating at the moment tested with HCl solution